(3cJGH aj GdUfGYI GdYXeis - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3BjGJ Gddg cd MbGFb GdCTjGA hMUfc ef THg GdBQGA Ef GdPi SCdJ QSeg ai GdUfGYI GdcHQi YfOeG QCjJ ef TOI GdCSJZdGb deG QSeg HWdjehS GdbdhPi s
(3BNQgG (B:s
(3GHOC ai Gdadc GdPi jLhR GdMQcI GdChdi hJLOgG GdeNWhW Ydi CbWGH Gdadcjf ced hJe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJH jYbhH gPG GdcJGH Edi GHfgs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs